Psychology 2011 : psychology of human development. Child abuse and neglect - Memorial University of Newfoundland. Extension Service; Peterson, Carole, 1942- (Memorial University of Newfoundland. Extension Service, 1977)
Dr. Carole Peterson discusses child abuse and neglect, focussing primarily on non-sexual abuse. Lacks closing credits. Minor distortion throughout.